Determining the Risk of Developing Rheumatic Heart Disease Following a Negative Screening Echocardiogram - Zimmerman, Meghan; Scheel, Amy; DeWyer, Alyssa; Nambogo, Jane-Liz; Otim, Isaac Omara; Tompsett, Alison; Rwebembera, Joselyn; Okello, Emmy; Sable, Craig; Beaton, Andrea (Frontiers in Cardiovascular Medicine, 2021)
Background: Screening echocardiograms can detect early-stage rheumatic heart disease (RHD), offering a chance to limit progression. Implementation of screening programs is challenging and requires further research. This is the first large-scale study assessing the risk of RHD among previous screen-negative children. Methods: This retrospective cohort study, conducted in Gulu, Uganda, performed school-based echo screening on children ages 5-18 years. Surveys were used to determine which children underwent initial screening 3-5 years prior. Age, gender, and disease severity were compared between cohorts. Relative risk (RR) of RHD was calculated for those with a prior screen-negative echo (exposed cohort) compared to those undergoing first screening (unexposed cohort). Results: Echo screening was completed in 75,708 children; 226 were excluded, leaving 1,582 in the exposed cohort and 73,900 in the unexposed cohort. Prevalence of new RHD was 0.6% (10/1,582) and 1% (737/73,900), in the exposed and unexposed cohorts, respectively. The RR of RHD was 0.64 (95% CI 0.3-1.2, p=0.15), a nearly 40% reduced risk of RHD in those with a prior negative echo. There was no difference in age or gender between RHD cohorts. All cases in the exposed cohort were borderline/mild; 2.6% of cases in the unexposed cohort had moderate/severe disease. Conclusion: There was no statistical difference in RHD prevalence between previous screen-negative children and children with no prior echocardiogram, however, there was a trend towards decreased risk and severity. This information has important implications for the design of screening programs and the use of screening echocardiograms in endemic RHD regions.